2007
DOI: 10.1590/s1807-59322007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Plasma Monitoring in Children Submitted to Surgery of Tetralogy of Fallot by a Micromethod Using High Performance Liquid Chromatography

Abstract: Sanches C, Galas FRBG, Silva AGO de M, Carmona MJC, Auler Jr. JO, Santos SRCJ. Propranolol plasma monitoring in children submitted to surgery of tetralogy of Fallot by a micromethod using high performance liquid chromatography. Clinics. 2007;62(3):215-24. OBJECTIVE:To evaluate the analytical micromethod using liquid chromatography for the quantification of propranolol in children submitted to surgery of tetralogy of Fallot (TLF). Methods: Only 0.2 mL of plasma is required for the assay. Peaks eluted at 8.4 (Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[5][6][7][8] However, in children, especially infants, such information is limited. 9,10 In a previous study, body weight-normalized oral clearance was similar in infants as in adults. 11 In this retrospective post hoc analysis we developed a population pharmacokinetic model to describe propranolol pharmacokinetics in infantile hemangioma patients and identified potential sources of pharmacokinetics variability.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…[5][6][7][8] However, in children, especially infants, such information is limited. 9,10 In a previous study, body weight-normalized oral clearance was similar in infants as in adults. 11 In this retrospective post hoc analysis we developed a population pharmacokinetic model to describe propranolol pharmacokinetics in infantile hemangioma patients and identified potential sources of pharmacokinetics variability.…”
mentioning
confidence: 78%
“…In adults, the pharmacokinetic properties of propranolol hydrochloride are well known . However, in children, especially infants, such information is limited . In a previous study, body weight–normalized oral clearance was similar in infants as in adults…”
mentioning
confidence: 96%
“…Studies have shown that patients on long-term propranolol at the time of corrective surgery are not at a disadvantage, 24 , 25 although Barazzone et al 26 demonstrated that the effects of isoproterenol were blunted but could be overcome by giving higher doses of the adrenergic agent. To avoid intra-operative problems, Garson et al 22 discontinued propranolol 4 days before surgery, but this risks having hypercyanotic spells before or even during surgery.…”
Section: β-Adrenergic Blockadementioning
confidence: 99%
“…In infants, limited information was available on the pharmacokinetic profile and plasma exposure of propranolol after oral administration. Until 2013, only 92 plasma concentrations observed after oral administration of propranolol in children from 8 weeks‐ to 13 years‐old were documented in 3 publications: mean concentrations ranged between 0.05 and 57 ng mL −1 for different doses and regimen . In 2013, published results in 4 term and 23 preterm neonates treated with oral propranolol at 0.25 or 0.5 mg kg −1 every 6 hour in which 1000 concentrations were measured by serial dried blood spots.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2013, only 92 plasma concentrations observed after oral administration of propranolol in children from 8 weeks-to 13 years-old were documented in 3 publications: mean concentrations ranged between 0.05 and 57 ng mL À1 for different doses and regimen. 32,34,40 In 2013, 14 published results in 4 term and 23 preterm neonates treated with oral propranolol at 0.25 or 0.5 mg kg À1 every 6 hour in which 1000 concentrations were measured by serial dried blood spots. After 0.5 mg/kg/6 hour, the mean maximum concentrations were 71.7 AE 29.8 ng mL À1 .…”
Section: Introductionmentioning
confidence: 99%